ANALISIS KEMAMPUAN PEMECAHAN MASALAH DITINJAU DARI KEPERCAYAAN DIRI SISWA: KASUS TOPIK PERSAMAAN GARIS LURUS: ANALYSIS OF PROBLEM-SOLVING ABILITY AS SEEN IN THE REASON OF STUDENTS' SELF-CONFIDENCE: CASE STUDY ON THE TOPIC OF STRAIGHT LINE EQUATIONS - Pemu, Nasrullah (KAMBIK: Journal of Mathematics Education, 2024)
This study aims to reveal the relationship between self-confidence and mathematical problem-solving ability experienced by students for straight line equation material. This research was conducted using quantitative and qualitative methods where the subjects involved were 30 students of SMPN 7 Barru. The instruments used were questionnaires, math problems, and interview guidelines. The results showed that subjects with a high level of self-confidence showed a more thorough fulfillment of the criteria than other subjects. Even subjects classified as moderate and low levels of self-confidence are still more lacking to fulfill the aspects reviewed in this search. What can be compared between the three subjects is that they can identify the information provided with equally good ability. However, the ability to determine the concept used, the subject with a moderate level of confidence was not as good as the other two subjects. Similarly, for the subject with a low level of self-confidence, in determining the relationship with other subjects and confidence in the answers he gave was not better than the other two subjects.